Equity, Climate Adaptation, and Urban Planning: A Case Study of Cape Town. - Teferra, Axum. (2017)
Abstract: This thesis examines how social equity manifests in urban climate change planning. As cities begin to experience the effects of climate change, many municipalities are taking steps to adapt by mainstreaming adaptation policies into all departments, but what role does social equity play? Vulnerabilities and risks are not equally shared by cities' residents; the urban poor are least responsible for increased greenhouse gas emissions, yet they may be most afflicted by and least resilient to the impacts of climate change. A case study of Cape Town, South Africa, provides a local-level examination of adapting housing settlements and land-use planning in a post-apartheid city, and demonstrates opportunities to synergize goals of climate change planners and social equity proponents. The study finds that combining goals of sustainable development and poverty alleviation, rather than keeping them in competing silos, can yield projects that are pro-poor and facilitate adaptation to climate change.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Julian Agyeman.; Keyword: Urban planning.